Isolation of Asphaltene-Degrading Bacteria from Sludge Oil - Aditiawati, Pingkan; Kamarisima, (Makara Journal of Science, 2015)
Sludge oil contains 30%–50% hydrocarbon fractions that comprise saturated fractions, aromatics, resins, and asphaltene. Asphaltene fraction is the most persistent fraction. In this research, the indigenous bacteria that can degrade asphaltene fractions from a sludge oil sample from Balikpapan that was isolated using BHMS medium (Bushnell-Hass Mineral Salt) with 0.01% (w/v) yeast extract, 2% (w/v) asphaltene extract, and 2% (w/v) sludge oil. The ability of the four isolates to degrade asphaltene fractions was conducted by the biodegradation asphaltene fractions test using liquid cultures in a BHMS medium with 0.01% (w/v) yeast extract and 2% (w/v) asphaltene extract as a carbon source. The parameters measured during the process of biodegradation of asphaltene fractions include the quantification of Total Petroleum Hydrocarbon (g), log total number of bacteria (CFU/ml), and pH. There are four bacteria (isolates 1, 2, 3, and 4) that have been characterized to degrade asphaltic fraction and have been identified as Bacillus sp. Lysinibacillus fusiformes, Acinetobacter sp., and Mycobacterium sp., respectively. The results showed that the highest ability to degrade asphaltene fractions is that of Bacillus sp. (isolate 1) and Lysinibacillus fusiformes (Isolate 2), with biodegradation percentages of asphaltene fractions being 50% and 55%, respectively, and growth rate at the exponential phase is 7.17x107 CFU/mL.days and 4.21x107 CFU/mL.days, respectively.